2023
DOI: 10.1155/2023/5497731
|View full text |Cite
|
Sign up to set email alerts
|

Superelastic Conical Friction Pendulum Isolator for Seismic Isolation of Bridges under Near-Fault Ground Motions

Abstract: To improve the seismic performance of bridges, this study develops a novel superelastic conical friction pendulum isolator (SCFPI) by incorporating an improved conical friction pendulum isolator (CFPI) with shape memory alloy (SMA). The flat sliding function designed for the improved conical friction pendulum isolator is to enhance the adaptability under service loadings. The analytical model of the novel SCFPI is derived and the numerical model is developed within the OpenSees platform to investigate the hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In addition, a re-centering seismic isolator [15] was developed by combining dampingenhanced sliding lead-rubber bearings with superplastic shape memory alloy. In addition, pendulum isolators with variable stiffness [16], conical friction pendulum isolators [17], and variable friction pendulum isolators [18,19] have been developed to improve the effectiveness of vibration isolation. Studies have demonstrated that low horizontal stiffness of isolators is required for effective vibration isolation when subjected to low-frequency ground motions [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a re-centering seismic isolator [15] was developed by combining dampingenhanced sliding lead-rubber bearings with superplastic shape memory alloy. In addition, pendulum isolators with variable stiffness [16], conical friction pendulum isolators [17], and variable friction pendulum isolators [18,19] have been developed to improve the effectiveness of vibration isolation. Studies have demonstrated that low horizontal stiffness of isolators is required for effective vibration isolation when subjected to low-frequency ground motions [20][21][22].…”
Section: Introductionmentioning
confidence: 99%